Human Rights and Decolonisation - Quentin-Baxter, Alison (Victoria University of Wellington Law Review, 1999)
This article provides a brief introduction to Professor RQ Quentin-Baxter and Alison Quentin-Baxter's papers found in this journal. They reveal insights which the authors derived from their personal involvement in areas of both national and international decision-making: the international implementation of human rights, and the transformation of Niue from its position as a colony to a self-governing state in a relationship of free association with New Zealand.